Sedum dormiens (Crassulaceae, Sempervivoideae, Sedeae): a new species from the Sierra de Manantlán, Mexico - Cuevas-Guzmán, Ramón; Pérez-Calix, Emmanuel; Carrillo-Reyes, Pablo (Phytotaxa, 2022)
Sedum dormiens (Crassulaceae) from the Sierra de Manantlán in Jalisco, Mexico, is described. The distinctive characters of the species are its chamaephytic nature, capillary roots, formation of large colonies, tetramerous flowers with white petals, dormant terminal and lateral buds in the mother plant and connate fruits of ½–¾ its length. The habitat and morphology of the species is illustrated and its relationships with close species presented. Its conservation status was categorized as Endangered (EN).